![\sqrt{x} + \sqrt{x - \sqrt{1 - x} } = 1 \sqrt{x} + \sqrt{x - \sqrt{1 - x} } = 1](https://tex.z-dn.net/?f=+%5Csqrt%7Bx%7D++%2B++%5Csqrt%7Bx+-++%5Csqrt%7B1+-+x%7D+%7D++%3D+1)
please give complete steps
Answers
Answered by
5
Answer :-
Transposing √x on RHS :-
Squaring on both side :-
Squaring on both side :-
Squaring on both side :-
Answered by
1
Step-by-step explanation:
√x-√1-x =1-√x
(√x-√1-x)²= (1-√x)²
x-√-x=(1-√x)²
x-√1-x=(1)²+(√x)²-2*1*√x
x-√1-x=1+x-2√x
x-x-√1-x=1-2√x
Now x will be cancled by x
-√1-x=1-2√x
(-√1-x)²=(1-2√x)²
repeat the same procedure to the right hand side expression and then simplify it further.
1-x=(1)²+2√x²-2* 1*2√x
1-x=1+4x-4√x
1-1-x =4x-4√x
1-1-x=4x-4√x
Now 1 will be cancled by 1
-x=4x-4√x
4√x=4x+x
4√x=5x
4√x²=5x²
16x=25x²
16x-25x²=0
x(25x-16) =0
Therefore,x = 0 or25x-16 = 0 is the solution of this equation.
x = 0 or x=16/25
putting x=0
√x+√x-√1-x=√0+√0-√1-0
0+√0-1
√-1
=>√-1≠1
now,putting x=16/25
Attachments:
![](https://hi-static.z-dn.net/files/d2b/fe421a8773958bded568db4f673986ca.png)
![](https://hi-static.z-dn.net/files/d1b/3771bce8c0b42b5be4b4e0d0cf13515e.png)
Similar questions
Environmental Sciences,
2 months ago
Chemistry,
2 months ago
Math,
2 months ago
Math,
4 months ago
Math,
4 months ago
Computer Science,
11 months ago
History,
11 months ago
English,
11 months ago